Food choices and macro- and micronutrient intake of Sowetans with chronic heart failure - Pretorius, Sandra S. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Rehabilitation))--University of Stellenbosch, 2011.